Ichthyofaunal diversity of a Ramsar site in Kashmir Himalayas -Wular Lake - Mushtaq, S. T.; Balkhi, M. H.; Bhat , F. A.; Mushtaq, S. A. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2024)
The present study was undertaken in order to assess the current status of ichthyofaunal diversity of one of Asia’s largest freshwater lakes — Wular, India.  In this study the sampling was carried out every month at 5 different sites of Wular Lake which were selected on the basis of different ecological niches. A total of 738 fish species were collected during the entire study. The ichthyofaunal biodiversity observed in this study belonged to 2 orders, 2 families, 4 sub families and 6 genera. The carps viz. Cyprinus carpio (var. communis), Cyprinus carpio (var. specularis) and Carassius carassius contributed more than 82.52 % to the total catch by biomass and 50.79 % to the total catch by number. Shannon-Wiener diversity index showed maximum value (1.476) during summer and minimum value (1.195) during autumn. Similarly, Pielou’s Evenness index and Simpson’s dominance index also showed maximum values (0.856 and 0.645) in summer and minimum values (0.738 and 0.438) in autumn respectively. The study revealed that there was a drastic decline in the native Schizothorax due to encroachment, pollution and other anthropogenic disturbances. Many fish species that had been reported in the lake in the earlier studies were not reported in this study, indicating their disappearance from the lake. Keeping in view the progressively worse situation, there is an urgent need to take remedial steps to conserve the endangered native fish fauna of the lake in order to preserve its biodiversity from further degradation.